Getting the Reformation wrong : correcting some misunderstandings - Payton, James R., 1947- (Downers Grove, Ill. : IVP Academic, 2010)
Most students of history know that Martin Luther nailed his ninety-five theses to the Wittenberg Church door and that John Calvin penned the Institutes of the Christian Religion. However, the Reformation did not unfold in the straightforward, monolithic fashion some may think. It was, in fact, quite a messy affair. Using the most current Reformation scholarship, James R. Payton exposes, challenges and corrects some common misrepresentations of the Reformation. --from publisher description
The medieval call for reform -- The Renaissance : friend or foe? -- Carried along by misunderstandings -- Conflict among the reformers -- What the reformers meant by sola fide -- What the reformers meant by sola Scriptura -- How the Anabaptists fit in -- Reformation in Rome -- Changing direction : from the Reformation to Protestant scholasticism -- Was the Reformation a success? -- Is the Reformation a norm? -- The Reformation as triumph and tragedy.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Reformation; Reformation; RELIGION / Christian Church / History; RELIGION / Christianity / History; Electronic books